Alternative staging of regional lymph nodes in gastric cancer - Szczepanik, Antoni M.; Paszko, Agata; Szura, Miroslaw; Scully-Horner, Thecla; Kulig, Jan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
The TNM pN stage based on the number of metastatic lymph nodes is an independent prognostic factor in gastric cancer. Many studies have highlighted the phenomenon of stage migration and problems in comparing groups of patients with different numbers of total lymph nodes harvested within TNM staging. The current version of UICC/AJCC and JGCA TNM classifications postulates a minimal number of 16 lymph nodes as the base for N stage determination. Alternative systems such as lymph node ratio (LNR), positive to negative lymph node ratio (PNLNR), and LOGODDS (or LODDS), were implemented to increase the quality of LN assessment. These methods have reached the background in the literature, but to date no standard approach according to the cut-offs for the stages has been implemented. LOGODDS is the method that most reflects the number of harvested lymph nodes. The rationale for alternative staging methods, their correlations, and limitations are presented.